Pyrene-labeled dendrimers functionalized with fullerene C60or porphyrincore as light harvesting antennas - Vonlanthen, Mireille (2018)
Pyrene-labeled dendrimers linked to a fullerene C60or a porphyrin core were designed and synthesized througha convergent synthetic pathway. The energy transfer process that is occuring inside the obtained dendrimers wasstudied by measuring and analysing their absorbance andfluorescence emission properties. All absorptionspectra are showing the typical absorption band of pyrene. No ground state interaction was detected betweenpyrene and porphyrin whereas a slight interaction was observed between pyrene and fullerene C60. An almostquantitative quenching of the pyrenefluorescence emission was observed when coupled with fullerene C60aswell as with porphyrin, indicating effective energy transfer. In the case of fullerene C60, no emission could beseen due its weak intrinsic emission. When the acceptor was a porphyrin moiety,fluorescence emission wasobserved from the free porphyrin as well as from the Zn complex analogue.